Functional Verification of Novel ELMO1 Variants by Live Imaging in Zebrafish - Xue, Rongtao; Wang, Ying; Wang, Tienan; Lyu, Mei; Mo, Guiling; Fan, Xijie; Li, Jianchao; Yen, Kuangyu; Yu, Shihui; Liu, Qifa; Xu, Jin (Frontiers in Cell and Developmental Biology, 2021)
ELMO1 (Engulfment and Cell Motility1) is a gene involved in regulating cell motility through the ELMO1-DOCK2-RAC complex. Contrary to DOCK2 (Dedicator of Cytokinesis 2) deficiency, which has been reported to be associated with immunodeficiency diseases, variants of ELMO1 have been associated with autoimmune diseases, such as diabetes and rheumatoid arthritis (RA). To explore the function of ELMO1 in immune cells and to verify the functions of novel ELMO1 variants in vivo, we established a zebrafish elmo1 mutant model. Live imaging revealed that, similar to mammals, the motility of neutrophils and T-cells was largely attenuated in zebrafish mutants. Consequently, the response of neutrophils to injury or bacterial infection was significantly reduced in the mutants. Furthermore, the reduced mobility of neutrophils could be rescued by the expression of constitutively activated Rac proteins, suggesting that zebrafish elmo1 mutant functions via a conserved mechanism. With this mutant, three novel human ELMO1 variants were transiently and specifically expressed in zebrafish neutrophils. Two variants, p.E90K (c.268G>A) and p.D194G (c.581A>G), could efficiently recover the motility defect of neutrophils in the elmo1 mutant; however, the p.R354X (c.1060C>T) variant failed to rescue the mutant. Based on those results, we identified that zebrafish elmo1 plays conserved roles in cell motility, similar to higher vertebrates. Using the transient-expression assay, zebrafish elmo1 mutants could serve as an effective model for human variant verification in vivo.